2006
DOI: 10.1128/jvi.00237-06
|View full text |Cite
|
Sign up to set email alerts
|

Gammaherpesvirus Persistence Alters Key CD8 T-Cell Memory Characteristics and Enhances Antiviral Protection

Abstract: In herpesvirus infections, the virus persists for life but is contained through T-cell-mediated immune surveillance. How this immune surveillance operates is poorly understood. Recent studies of other persistent infections have indicated that virus persistence is associated with functional deficits in the CD8 ؉ T-cell response. To test whether this is the case in a herpesvirus infection, we used a mutant murine gammaherpesvirus that is defective in its ability to persist in the host. By comparing the immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 66 publications
7
59
0
Order By: Relevance
“…As shown in Fig. 1A and B, wild-type (WT) and IFNAR1 Ϫ/Ϫ mice had similar early kinetics of expansion of CD8 ϩ T cells specific for these two viral epitopes, with expansion of p56-specific CD8 ϩ T cells preceding expansion of p79-specific CD8 ϩ T cells as previously described (18)(19)(20). However, IFNAR1 Ϫ/Ϫ mice had approximately 2-to 4-fold-higher levels of p56-specific CD8 ϩ T cells beginning at 16 dpi and as late as 46 dpi and approximately 2-to 3-fold-higher levels of p79-specific CD8…”
Section: Type I Ifn Signaling-deficient Mice Have Increased Numbers Omentioning
confidence: 84%
“…As shown in Fig. 1A and B, wild-type (WT) and IFNAR1 Ϫ/Ϫ mice had similar early kinetics of expansion of CD8 ϩ T cells specific for these two viral epitopes, with expansion of p56-specific CD8 ϩ T cells preceding expansion of p79-specific CD8 ϩ T cells as previously described (18)(19)(20). However, IFNAR1 Ϫ/Ϫ mice had approximately 2-to 4-fold-higher levels of p56-specific CD8 ϩ T cells beginning at 16 dpi and as late as 46 dpi and approximately 2-to 3-fold-higher levels of p79-specific CD8…”
Section: Type I Ifn Signaling-deficient Mice Have Increased Numbers Omentioning
confidence: 84%
“…6D). This was somewhat surprising since MHV-68-specific memory CD8 ϩ T cells have more frequent encounters with Ag and exhibit a more effector memory cell phenotype (41), and it has been shown in vitro that effector cells have lower requirements for costimulation (63).…”
Section: Discussionmentioning
confidence: 99%
“…MHV-68 establishes a low-level persistent infection and memory CD8 ϩ T cells specific for the virus exhibit unique characteristics distinct from that of memory cells in acute viral infections (41). We have previously reported that MHV-68 ORF61-specific memory CD8 ϩ T cells require CD28 costimulation to elicit a robust recall response (22).…”
Section: Cd28 Costimulation Is Required For Secondary Responses Of Mementioning
confidence: 99%
“…Our experiments examining the arming of NK cells, as well as previous experiments that uncovered heightened resistance against Listeria monocytogenes during herpesvirus latency, 18 made use of the latency-defective MuHV-4 mutant O73.stop. This virus replicates to normal 22,28 or near-normal levels 23 during acute infection but is severely defective in its ability to persist in the latent state. NK-cell activation is equivalent for wild-type MuHV-4 and O73.stop during acute infection.…”
Section: Discussionmentioning
confidence: 99%